2016
DOI: 10.1007/s00414-016-1343-2
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of crimes by infrared photography

Abstract: Whenever blunt or sharp forces are used in a crime, analysis of bloodstain pattern distribution may provide important information for the reconstruction of happenings. Thereby, attention should be paid to both the crime scene and the clothes of everyone involved in the crime. On dark textiles, though, it is difficult or even impossible for the human eye to detect bloodstains because of the low contrast to the background. However, in the near infrared wavelength range, contrast is considerably higher. Many text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This study found IR is a viable option when looking for blood on dark fabrics and often performs better despite the maximum absorption of blood being around 410 nm. This is because the fabric reflects the IR light at about 830 nm and we are left with a gray to white background and a dark in color stain [5]. However, when searching for blood on new clothing there are chemical additives that may alter the appearance of blood under ALS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found IR is a viable option when looking for blood on dark fabrics and often performs better despite the maximum absorption of blood being around 410 nm. This is because the fabric reflects the IR light at about 830 nm and we are left with a gray to white background and a dark in color stain [5]. However, when searching for blood on new clothing there are chemical additives that may alter the appearance of blood under ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature reports that blood experiences the greatest absorption of light around 410 nm and will appear much darker than its surrounding fabric [2][3][4]. Research shows that fabrics reflect light that is greater than 830 nm [5], so IR can be an incredibly valuable wavelength when searching for evidence. IR has been discussed in forensic science books since 1961 but was not widely used until the digital era because the film was expensive [6].…”
Section: Jamesmentioning
confidence: 99%
“…This is a kind of operation which is very easy and there are different types of systems there through which it can be used (Kanbar, 2016). There are two ways which are called the basics like stitching and the exporting which can be done in an automated way (Sterzik and Bohnert, 2016). There are two things which are called as the indication and the distortion which can be minimized with the use of the smart software.…”
Section: Factors To Consider the User Experiencementioning
confidence: 99%